Conservation medicine and One Health in zoos: Scope, obstacles, and unrecognized potential. Issue 1 (22nd September 2020) - Sulzner, Kate; Fiorello, Christine; Ridgley, Frank; Garelle, Della; Deem, Sharon L.
Abstract: Zoo veterinarians and allied professionals have been contributing to conservation medicine (CM) and One Health (OH) activities for more than two decades. Although the Association of Zoos and Aquariums (AZA) considers conservation a key part of its mission, little published material exists about the extent of AZA work in CM/OH or the challenges and opportunities associated with these endeavors. To better understand the current scope of CM/OH in zoos, we surveyed 53 AZA‐accredited institutions from April through October of 2016. We obtained information on CM/OH infrastructure, support for expansion in this area, and strategies to overcome perceived obstacles hindering CM/OH from becoming a core AZA activity. Survey results revealed that while most zoos favor greater investment in CM/OH programs, awareness, and understanding of CM/OH across the broader zoo community and public is lacking. The majority of respondents stated that overcoming this challenge is paramount to attaining support for CM/OH initiatives. In spite of these obstacles, survey respondents highlighted many positive developments in CM/OH. We found that 84% of zoos surveyed are actively engaged in CM/OH activities, and 12% house formal CM/OH programs. Another 8% of respondents said their institutions were developing CM/OH programs. Perhaps most noteworthy, we found that zoo size did not have a significant bearing on the financial amount allocated toward an institution's CM/OH activities. This suggests that all zoos, regardless of size, can make meaningful contributions to the growing movement of CM/OH and help redefine the role of zoos within this movement. Abstract : The graphical abstract depicts the growth and impact potential of AZA institutions in conservation medicine (CM) and One Health (OH) if greater support in the areas highlighted were directed toward this effort (top image) versus the challenges hindering development, visibility, and contributions of zoos and aquariums in the CM/OH movement (bottom image). Research Highlight: In a survey of 53 Association of Zoos and Aquariums institutions, our findings revealed that despite funding and infrastructure constraints, zoos and aquariums are poised to play a meaningful role in the growing conservation medicine/One Health movement.